Retrograde Amnesia and Disorientation after Intraocular Injection of Anti-VEGF Agents - Meyer, Peter-Wolfgang; N. Ungerer, Matthias; Schröder, Johannes (Journal of Neurological Research And Therapy, 2018)
We present a case of a 77-year-old male patient who was treated in our outpatient clinic for memory disorders because of episodic confusion and retrograde amnesia. The patient reported having symptoms repeatedly following intraocular treatment with Anti-Vascular Endothelial Growth Factor Agents (Ranibizumab and Bevacizumab) as a treatment for wet macular degeneration. EEG showed a localized deceleration that intensified under prolonged voluntary hyperventilation. Symptoms resolved after the intraocular Anti-Vascular Endothelial Growth Factor treatment was stopped and anticonvulsive treatment with lamotrigine was begun. This case is important in that it describes a potential association between intraocular treatments with Anti-Vascular Endothelial Growth Factor Agents and seizures. Symptoms occurred in temporal correlation with intraocular treatment. Clinicians should be aware of this potential side effect on intraocular treatment with Anti-Vascular Endothelial Growth Factor Agents in patients with high risk for seizures.
Keywords: macular degeneration; intraocular treatment; Anti-Vascular Endothelial Growth Factor; Ranibizumab; Bevacizumab; confusion